3D Carbon Scaffolds for Neural Stem Cell Culture and Magnetic Resonance Imaging. Issue 4 (21st December 2017) - Fuhrer, Erwin; Bäcker, Anne; Kraft, Stephanie; Gruhl, Friederike J.; Kirsch, Matthias; MacKinnon, Neil; Korvink, Jan G.; Sharma, Swati
Abstract: 3D glassy carbon structures with percolated macropores are obtained by pyrolysis of chemically synthesized cryogels featuring tunable porosity. These batch‐fabricated structures are used as scaffolds for culturing neural stem cells (NSCs) and are characterized by magnetic resonance imaging (MRI). With the aid of MRI, the successful cultivation of NSCs on a glassy carbon surface and the precise 3D locations of these cell clusters within the opaque scaffold are demonstrated. MRI also yields pore morphology and porosity analyses, pre‐ and post‐pyrolysis. This integrated approach yields a complete 3D dataset of the NSC network, which enables the visual inspection of the morphological details of individual cell clusters without disturbing them or destroying the scaffold. Reported experimental methodology is expected to have an impact on studies designed to understand the mechanism of neurodegenerative disease (ND) development, and can serve as a protocol for the culture of various other types of cells that display compatibility with glassy carbon surfaces. Abstract : Neural stem cells cultured on 3D glassy carbon scaffolds are noninvasively characterized by high‐resolution magnetic resonance imaging (MRI). Scaffolds are obtained from pyrolysis of porous cryogels, opening the potential for tailoring the scaffold morphology as dictated by the cellular microenvironment. MRI data are further processed to yield spectacular videos and reconstructed images where individual cell clusters can be identified.